(untitled) (Universal International Scientific Journal, 2026)
This article examines the complex interplay between cognitive and motivational mechanisms that facilitate students’ self-activation in contemporary university learning environments. Self-activation, defined as the autonomous initiation and maintenance of learning behaviors, represents a critical factor in academic success and lifelong learning competence. Drawing on self-determination theory, cognitive load theory, and contemporary motivation research, this study explores how internal psychological processes and external environmental factors converge to influence students’ capacity for self-directed learning engagement. The results suggest that educational interventions aimed at enhancing student self-activation should simultaneously address cognitive skill development, motivational climate optimization, and the structural features of learning environments that either facilitate or constrain autonomous learning engagement.